2011
DOI: 10.1111/j.1469-8137.2011.03848.x
|View full text |Cite|
|
Sign up to set email alerts
|

The diel imprint of leaf metabolism on the δ13C signal of soil respiration under control and drought conditions

Abstract: Summary• Recent 13 CO 2 canopy pulse chase labeling studies revealed that photosynthesis influences the carbon isotopic composition of soil respired CO 2 (d 13 C SR ) even on a diel timescale. However, the driving mechanisms underlying these short-term responses remain unclear, in particular under drought conditions.• The gas exchange of CO 2 isotopes of canopy and soil was monitored in drought ⁄ nondrought-stressed beech (Fagus sylvatica) saplings after 13 CO 2 canopy pulse labeling. A combined canopy ⁄ soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 56 publications
6
64
3
Order By: Relevance
“…Short-term storage under control conditions might have been responsible for this observation, supported by Bahn et al (2013) who found a large and fast 13 C incorporation into starch which was subsequently used in the following night. Such transitory starch plays a large role as substrate for nocturnal respiration, as shown for example by Barthel et al (2011a) for beech saplings (Fagus sylvatica) and for thale cress (Arabidopsis thaliana) in laboratory experiments (Zeeman et al, 2007). However, in our study, 13 C excess in shoots decreased rather slowly during the first four days after labeling.…”
Section: Below-ground Carbon Allocation Under Control Conditionscontrasting
confidence: 47%
See 1 more Smart Citation
“…Short-term storage under control conditions might have been responsible for this observation, supported by Bahn et al (2013) who found a large and fast 13 C incorporation into starch which was subsequently used in the following night. Such transitory starch plays a large role as substrate for nocturnal respiration, as shown for example by Barthel et al (2011a) for beech saplings (Fagus sylvatica) and for thale cress (Arabidopsis thaliana) in laboratory experiments (Zeeman et al, 2007). However, in our study, 13 C excess in shoots decreased rather slowly during the first four days after labeling.…”
Section: Below-ground Carbon Allocation Under Control Conditionscontrasting
confidence: 47%
“…Which of the two alternative explanations, (1) a higher residence time of fresh assimilates in the above-ground biomass as observed for beech saplings under drought (Ruehr et al, 2009) or (2) a higher relative below-ground allocation of recent assimilates as had been shown under laboratory conditions (Sanaullah et al, 2012 for grasses, Barthel et al, 2011a for beech saplings) is responsible for such a reduced coupling remains to be investigated. Independent of the exact distribution within the plant, we anticipated the use of fresh assimilates in soil CO 2 efflux to be reduced under drought conditions (Ruehr et al, 2009;Barthel et al, 2011a).…”
Section: S Burri Et Al: Drought Impact On Short-term Carbon Cyclingmentioning
confidence: 94%
“…However, from correlation-based flux studies it is not consistently clear to which extent they are temperature-(and moisture-) independent and thus possibly related to rapid allocation of C from recent photosynthesis to respiration (Tang et al, 2005;Bahn et al, 2008;Subke and Bahn, 2010;Vargas et al, 2010;Philipps et al, 2011). It is also not clear to which extent these diel variations of δ 13 C of soil CO 2 efflux reflect the number of processes potentially involved, including changes in vapor pressure deficit that affect photosynthetic discrimination against 13 C (Brugnoli et al, 1988;Farquhar et al, 1989; see 2.1), changes in respiratory C isotope fractionation as demonstrated for CO 2 respired by leaves (Hymus et al, 2005) as well as trunks (Kodama et al, 2008), diurnal changes in respiratory carbon source Gessler et al, 2007;Bahn et al, 2009;Barthel et al 2011) and diffusion processes (Moyes et al, 2010). For a detailed mechanistic analysis of the origin of diel variations in the δ 13 C see .…”
Section: Temporal C Allocation Patternsmentioning
confidence: 99%
“…Recently, it was demonstrated that drought stress not only reduced C assimilation but often also increased the mean residence time of recently assimilated C in leaf biomass; furthermore, the C transfer velocity was reduced in saplings and the trunk of some tree species, leading to a reduced coupling between canopy photosynthesis and belowground processes under water stress (Ruehr et al, 2009;Barthel et al 2011;Dannoura et al, 2011). Similarly, shading has been shown to reduce the speed of link between photosynthesis and soil respiration in grassland (Bahn et al, 2009).…”
Section: Sensitivity Of C Allocation To Environmental Stressmentioning
confidence: 99%
“…In just a few years, the DREAM algorithm has found widespread application and use in numerous different fields, including (among others) atmospheric chemistry (Partridge et al, 2011(Partridge et al, , 2012, biogeosciences (Scharnagl et al, 2010;Braakhekke et al, 2013;Ahrens and Reichstein, 2014;Dumont et al, 2014;Starrfelt and Kaste, 2014), biology (Coelho et al, 2011;Zaoli et al, 2014), chemistry (Owejan et al, 2012;Tarasevich et al, 2013;DeCaluwe et al, 2014;Gentsch et al, 2014), ecohydrology (Dekker et al, 2010), ecology (Barthel et al, 2011;Gentsch et al, 2014;Iizumi et al, 2014;Zilliox and Goselin, 2014), economics and quantitative finance (Bauwens et al, 2011;Lise et al, 2012;Lise, 2013), epidemiology (Mari et al, 2011;Rinaldo et al, 2012;Leventhal et al, 2013), geophysics (Bikowski et al, 2012;Linde and Vrugt, 2013;Carbajal et al, 2014;Lochbühler et al, 2014Lochbühler et al, , 2015, geostatistics (Minasny et al, 2011;Sun et al, 2013), hydrogeophysics (Hinnell et al, 2011), hydrologeology (Keating et al, 2010;Laloy et al, 2013;Malama et al, 2013), hydrology (Vrugt et al, 2008a(Vrugt et al, , 2009a…”
Section: Introduction and Scopementioning
confidence: 99%